Implementation of Lean Manufacturing to increase Company Production Efficiency - Suwanda Suwanda (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2023)
Lean Manufacturing is known as a management approach that focuses on eliminating waste, process efficiency, and increasing added value. This research aims to evaluate and apply the Lean Manufacturing concept as a strategy to improve production quality in a manufacturing organization. This research uses a qualitative approach with descriptive methods. The research results show that the application of Lean Manufacturing, especially through the concepts of waste elimination, value flow optimization, quality improvement, Just-In-Time (JIT) production, workforce involvement, production flexibility, and the 5S approach, has a positive impact on the operational efficiency of manufacturing companies . Eliminating waste, including excess inventory and unproductive production time, can reduce costs and increase productivity. Value stream mapping helps identify and eliminate waste in every stage of production. A focus on defect prevention and continuous improvement improves product quality, reduces the risk of remanufacturing, and increases customer satisfaction. JIT principles optimize production according to demand, reduce storage costs, and increase flexibility. Engaging the workforce in continuous improvement not only reduces waste but also increases productivity and morale. Lean's ability to respond to market changes and apply the 5S approach in organizing the work environment is also the key to success in improving the company's operational efficiency in a sustainable manner.